2002
DOI: 10.1051/0004-6361:20011626
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse far-infrared [$\ion{C}{ii}$] line emission from high Galactic latitude

Abstract: • ) of the Galactic plane are systematically larger than those on the northern side (b > 0 • ). We infer from this difference that there is a displacement of the Sun with respect to the center of interstellar medium from which the [C ii] line comes. When an exponential distribution is assumed for the [C ii] emitting gas, it is expected that the Sun is located at the distance of about 17% of the scale height above the center of the gas. This is consistent with the previously reported displacement of the Sun fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 43 publications
(36 reference statements)
0
25
0
Order By: Relevance
“…Makiuti et al (2002) conclude that the major source of the [C ii] line emission observed by IRTS/FILM at high Galactic latitudes is the WIM. However, the data and the interpretation for the high latitude diffuse [C ii] emission seen by COBE (cf.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations
“…Makiuti et al (2002) conclude that the major source of the [C ii] line emission observed by IRTS/FILM at high Galactic latitudes is the WIM. However, the data and the interpretation for the high latitude diffuse [C ii] emission seen by COBE (cf.…”
Section: Introductionmentioning
confidence: 79%
“…to larger values of b than BICE (Makiuti et al 2002), but FILM only observed [C ii] in a narrow strip along a great circle crossing the plane at l = 50…”
Section: Z-distribution Of [C Ii] Emission Gas Componentsmentioning
confidence: 95%
See 2 more Smart Citations
“…Nonetheless, BICE, with its 15 beam, was able to resolve peaks in intensity along several lines of sight. The FILM instrument on board IRTS (Shibai et al 1994;Makiuti et al 2002) had a beam size of 8 × 15 , and a velocity resolution comparable to FIRAS (∼750 km s −1 ), inadequate to resolve any velocity structure. It surveyed the Galaxy only along two 5 • wide bands forming a great circle on the sky.…”
Section: Introductionmentioning
confidence: 99%